Studi Variasi Morfologi Jenis Rotan Penghasil Jernang (Daemonorops spp.) Di Kecamatan Kuta Panang Kabupaten Aceh Tengah - Sendy Naya Putri; Saida Rasnovi; Rita Andini (Jurnal Ilmiah Mahasiswa Pertanian, 2020)
Kuta Panang is a sub-district in Central Aceh Regency, Aceh Province, Indonesia. Weh Nongkal Toa Village is one of the villages in Kuta Panang District with an area of ± 19,000 ha of Weh Nongkal Toa village. This study aims to identify the morphological characters of the rattan species that produces Daemonorops spp. and analyzing and comparing the significant differences in the morphological characters of Daemonorops spp. The object of the research was the rattan producing jernang ( Daemonorops spp.) Which consisted of three types, namely Daemonorops draco (Wild.) Blume, Daemonorops mattanensis Becc,Daemonorops didymophylla Becc. The method used in this research is to use qualitative and quantitative data research variables in which there are morphological characters in, 1). stem; (upright, plant height, stem diameter, number of stems, the length of the stem, stem color, segment length ( Internode ). 2). leaf; (leaf length, number of leaves, leaf color). 3). fruit; (fruit color, fruit diameter, number of fruits). 4). thorns; (thorn position, shortest thorn length, longest thorn, thorn color). ANOVA analysis was used as an analytical tool to test the research hypothesis whether there was an average difference between groups and the Bnt test to obtain the smallest significant difference. The results of quantitative data on stem height: D. draco 4 - 6 m, D. mattanensis 2 - 4 m,D. didymophylla 1 - 3 m, the length of the bunch, namely D. draco 3 - 4 m, D. mattanensis 1 - 3 m, and D. didymophylla 1 - 2 m. Stem diameter: D. draco 6-8 cm, D. mattanensis 3-6 cm, and D. didymophylla 1-3 cm. Internodes length: D. draco 15 - 40 cm, D. mattanensis 10 - 35 cm and D. didymophylla 8 - 30 cm. Leaf length: D. draco 30-45 cm, D. mattanensis 30-38 cm, and D. didymophylla 26-30 cm. Fruit diameter: D. draco 4 - 6 cm, D. mattanensis 2 - 4 cm, andD. didymophylla 2 - 3 cm. Long spines: D. draco 2 - 4 cm, D. mattanensis 2 - 3 cm, and D. didymophylla 1 - 2 cm. ANOVA test that was significantly different, namely the quantitative morphological characters of stem height, stem diameter length, bunch length, internode length, leaf length, and fruit diameter showed significantly different results between the three types of rattan producing jernang ( Daemonorops spp.), Whereas Morphological characters on the number of stems, number of leaves, number of fruit, length of the shortest thorn, and length of the longest thorn showed no significant difference between the three types of Daemonorops.spp. The very significant LSD test was the quantitative morphological characters of stem height, stem diameter, bunch length, internode length, leaf length, and fruit diameter.